Establishment of an in vitro cytotoxicity assay platform using primary monkey cardiomyocytes. (February 2019) - Iguchi, Takuma; Fujimoto, Kazunori; Nakamura, Shinichiro; Kishino, Hiroyuki; Niino, Noriyo; Mori, Kazuhiko
Abstract: To establish an in vitro cytotoxicity assay platform using monkey cardiomyocytes, we isolated primary cardiomyocytes from fetal cynomolgus monkeys at different gestation days (from day 39 to 90) using the trypsin and collagenase digestion method, which was identical to the standard procedure for rat cardiomyocytes. Under these conditions, the primary cells obtained from monkeys at gestation day 63 or earlier showed spontaneous beating, with >80% cells being viable from all fetuses. Transcriptome analysis of the monkey cardiomyocytes indicated that the cells have essential components of cardiac functions, such as myosins, α-actin, cardiac troponins, and calcium-related molecules. The susceptibility to doxorubicin-induced cytotoxicity in monkey cardiomyocytes was comparable to that in rat cardiomyocytes, as evaluated based on intracellular ATP levels. Microarray analysis with Ingenuity Pathway Analysis revealed that doxorubicin predominantly increased the expression of several key genes involved in the endoplasmic reticulum stress pathway in monkey cardiomyocytes than in rat cardiomyocytes. In conclusion, we isolated primary monkey cardiomyocytes that showed similar sensitivity to doxorubicin as compared with rat cardiomyocytes. This in vitro monkey cardiomyocyte assay platform would serve as a powerful tool for the investigation of the interspecies differences in drug-induced cardiotoxicity and its underlying mechanism. Highlights: An in vitro cytotoxicity assay using fetal monkey cardiomyocytes was established. The cytotoxicity towards doxorubicin was comparable between monkey and rat. Doxorubicin increased endoplasmic reticulum stress pathway in monkey cardiomyocytes.